2022
DOI: 10.1186/s12889-022-12561-x
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of residents’ environmental health literacy in Shaanxi province, China: a cross-sectional study

Abstract: Background This study comprehensively analyzed the basic conditions and influencing factors of the residents' environmental health literacy (EHL) level in Shaanxi Province, China in 2020, and provided a scientific basis for exploring new ideas and new methods to improve the EHL level of the whole people. Methods In the cross-sectional study with a multi-stage random sampling method, 1320 participants were recruited in 6 neighborhood committees (adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 19 publications
0
2
1
15
Order By: Relevance
“…Individuals in the urban district of Chiang Mai, as well as both the rural and urban districts of Lampang, showed higher levels of EHL compared to their counterparts in Chiang Mai’s rural district, which is home to a minority group. This observation is consistent with a study conducted in China, which found that rural residents had significantly lower EHL than those living in urban areas [ 23 , 31 ]. These results suggest that geographical location may play a role in influencing EHL levels among participants.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Individuals in the urban district of Chiang Mai, as well as both the rural and urban districts of Lampang, showed higher levels of EHL compared to their counterparts in Chiang Mai’s rural district, which is home to a minority group. This observation is consistent with a study conducted in China, which found that rural residents had significantly lower EHL than those living in urban areas [ 23 , 31 ]. These results suggest that geographical location may play a role in influencing EHL levels among participants.…”
Section: Discussionsupporting
confidence: 92%
“…The study found a positive association between higher education levels and enhanced EHL. This aligns with existing research that demonstrates a strong link between education and health literacy [ 23 , 31 , 32 ]. However, it is important to recognize that individuals with lower educational levels can also possess EHL.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, COVID-19 is more likely to occur in prosperous cities closer to the epicenter, located on higher altitudes, with high concentrations of air pollutants except NO 2 and O 3 , under conditions of extreme weather and high minimum relative humidity ( 19 ). Zhao et al ( 20 ) found the residents' environmental health literacy (EHL) level of urban residents is significantly higher than that of rural residents in Shaanxi Province, so they stressed the importance of education and popularizing basic environmental health knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…According to Gray et al [ 49 ] and Zhao et al [ 50 ], lower age should be significantly related to a higher HL value. We modified our regression model and exploratively tested whether age and the information sources “newspapers” and “TV commercials” showed a better fit (Model 2).…”
Section: Resultsmentioning
confidence: 99%